2019
DOI: 10.1002/aoc.5423
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2‐formylpyridine 4‐allyl‐S‐methylisothiosemicarbazone and Zn(II), Cu(II), Ni(II) and Co(III) complexes: Synthesis, characterization, crystal structure, antioxidant, antimicrobial and antiproliferative activity

Abstract: New zinc (II), copper (II), nickel (II) and cobalt (III) complexes, [Zn (HL)2]I2 (1), [Cu (HL)Cl2] (2), [Cu (HL)Br2] (3), [Cu (HL)(H2O)2](ClO4)2 (4), [Ni (HL)2]I2·H2O (5), [Co(L)2]Cl (6), [Co(L)2]NO3 (7), [Co(L)2]I·[Co(L)2](I3) (8) were obtained with 2‐formylpyridine 4‐allyl‐S‐methylisothiosemicarbazone (HL). The isothiosemicarbazone ligand was characterized by NMR (1H and 13C), IR spectroscopy and X‐ray diffraction. All the complexes were characterized by elemental analysis, IR, UV–Vis, ESI‐MS spectroscopy, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…According to the in vitro studies, cobalt(II)Pc and copper(II)Pc complexes, in particular, showed antibacterial activities against S. typhimurium and E. coli. Recently, a series of 2-formylpyridine 4-allyl-S-methylisothiosemicarbazone of zinc(II), copper(II), nickel(II) and cobalt(III) complexes were reported [110]. The in vitro tests showed that cobalt(III) complexes (43, Figure 9) were more active against Gram-positive bacteria (e.g., S. aureus) and fungal strains (C. albicans) with MIC values of 0.7-3 and 7-250 µg/mL, respectively, and less active against Gram-negative strains, such as E. coli and K. pneumoniae.…”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…According to the in vitro studies, cobalt(II)Pc and copper(II)Pc complexes, in particular, showed antibacterial activities against S. typhimurium and E. coli. Recently, a series of 2-formylpyridine 4-allyl-S-methylisothiosemicarbazone of zinc(II), copper(II), nickel(II) and cobalt(III) complexes were reported [110]. The in vitro tests showed that cobalt(III) complexes (43, Figure 9) were more active against Gram-positive bacteria (e.g., S. aureus) and fungal strains (C. albicans) with MIC values of 0.7-3 and 7-250 µg/mL, respectively, and less active against Gram-negative strains, such as E. coli and K. pneumoniae.…”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…In 1952, the first reported studies regarding the biological activity of cobalt complexes examined the toxicity of the optical isomers of [Co(en) 3 ](NO 3 ) 3 (en = ethylenediamine) [ 3 ]. Since then, many cobalt complexes of biological interest have been reported with the majority of them showing antiproliferative [ [4] , [5] , [6] , [7] ], antimicrobial [ [8] , [9] , [10] ], antifungal [ 11 , 12 ], antiviral [ 13 , 14 ], and antioxidant [ [15] , [16] , [17] ] activity.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previously reported coordination compounds of 2‐formilpyridine N 4 ‐allyl‐ S ‐methylisothiosemicarbazone [ 24 ] and other 3 d metal coordination compounds with S ‐alkylisothiosemicarbazones, [ 35 ] it was proved that 2‐acetylpyridine N 4 ‐allyl‐ S ‐methylisothiosemicarbazone can act as tridentate ligand with NNN or NNS set of donor atoms. Previously, the coordination of S ‐alkylisothiosemicarbazones through alkylated sulfur atom was observed only in case of some palladium coordination compounds.…”
Section: Resultsmentioning
confidence: 65%
“…In the related neutral 2‐formylpyridine N 4 ‐allyl‐ S ‐methylisothiosemicarbazone, the nitrogen atoms of pyridine and hydrazine fragments are translocated. [ 24 ] The iodine and nonhydrogen atoms of H 2 L except C 3 H 5 substituent in A and B are coplanar within 0.1 Å. In the crystal of polymorphs, the [H 2 L]I units form stack with antiparallel arrangement of organic molecules in A and about parallel in B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation